A century of James Frazer's The Golden bough
1 online resource
Keywords: "This multidisciplinary volume examines the ongoing effects of James G. Frazer's The Golden Bough in modern Humanities and its wide-ranging influence across studies of ancient religions, literature, historiography and reception studies. It begins by exploring the life and times of Frazer himself and the writing of The Golden Bough in its cultural milieu. The volume then goes on to cover a wide range of topics, including: ancient Near Eastern religion and culture; Minoan religion and in particular the origins of notions of Minoan matriarchy; Frazer's influence on the study of Graeco-Roman religion and magic; Frazer's influence on modern Pagan religions; and the effects of Frazer's works in modern culture and scholarship generally. Chapters examine how modern academia - and beyond - continues to be influenced by the otherwise discredited theories in The Golden Bough, ideas such as Sacred Marriage and the incessant Fertility of Everything. The book demonstrates how scholarship within the Humanities as well as practitioners of alternative religions and the common public remain under the thrall of Frazer over one hundred years since the publication of the abridged edition of The Golden Bough, and what we must do to shake off that influence. A Century of James Frazer's The Golden Bough is of interest to scholars and students from a wide range of disciplines, including Ancient History, History of Religion, Comparative Religion, Classical Studies, Archaeology, Historiography, Anthropology, Folklore, and Reception Studies"--